Answer:
[tex]x-2[/tex] is not a factor of [tex]p(x)=4x^2-3x+22[/tex].
Step-by-step explanation:
According to the factor theorem, if [tex]x-a[/tex] is a factor of [tex]p(x)[/tex], then [tex]p(a)=0[/tex].
Let [tex]p(x)=4x^2-3x+22[/tex]. If [tex]x-2[/tex] is a factor of [tex]p(x)=4x^2-3x+22[/tex], then [tex]p(2)=0[/tex].
Let us plug in [tex]x=2[/tex] in to the function to see if it will give us zero.
[tex]p(2)=4(2)^2-3(2)+22[/tex]
We simplify to obtain,
[tex]p(2)=4(4)-3(2)+22[/tex]
[tex]p(2)=16-6+22[/tex]
[tex]p(2)=10+22[/tex]
[tex]p(2)=32[/tex]
Since [tex]p(2)\ne0[/tex], [tex]x-2[/tex] is not a factor of [tex]p(x)=4x^2-3x+22[/tex].